Skills mismatch, automation, and training: Evidence from 17 European countries using survey data and online job ads - Yuchen Guo; Christina Langer; Fabio Mercorio; Francesco Trentini (EconPol Forum, 2022)
Linking survey data and online job ads offers new insights into skills gaps in the EU. Matching labor market needs and skill supply remains a Europe-wide challenge. Manual workers have skill supply shortages, cognitive workers have skill supply surpluses. Workers at higher risk of automation experience higher skill shortages, potentially because their job tasks are changing more rapidly. On-the-job training might be a potential measure to meet future skills needs.
Keywords: 330